Gentrified Discipline: The Impact of Gentrification on Exclusionary Punishment in Public Schools. (17th August 2021) - Pearman, Francis A
Abstract: This study examines the effects of gentrification on exclusionary punishment in urban schools across the United States. Integrating longitudinal data from the National Center for Education Statistics, the Civil Rights Data Collection, the U.S. Census, and the American Community Survey, this study estimates the effects of gentrification on suspensions, expulsions, law enforcement referrals, and school arrests through a series of negative binomial regression models. Results indicate that gentrification does not have broad or striking influences on school disciplinary environments overall, but it does promote modest increases in out-of-school suspensions as well as racial disparities in suspensions. Little evidence is found that effects vary by sex, grade level, or school racial composition. A battery of sensitivity analyses suggests that overall findings are generally robust to the presence of unobserved confounding and are broadly consistent across alternative model specifications and different measures of gentrification.